A. S. Byatt and the quiddity of things: a material-semiotic approach to narrating the human through the non-human. Issue 3 (4th March 2022) - Walezak, Emilie
ABSTRACT: This paper examines the evolution of A. S. Byatt's writing in her later works, from the 2000s to the present, in particular the increasing enmeshment of the human and the non-human in her apprehension of embodiment and embeddedness. Her short fiction helped her develop transcorporeal ontologies. It sheds light on the parallel endeavour in her novels to increasingly connect, on an epistemological level, the cross-breeding of scientific disciplines. The premise of this integrated approach is to be found in the highly conceptual novel from 2000, The Biographer's Tale, in which the first-person narrator's dissatisfaction with social constructionism initiates his quest: 'I must have things '. The writing project outlined at the end of the novel heralds Byatt's own later practice: 'I could mix warnings with hints, descriptions with explanations, science with little floating flashes of literature'. In her latest novel, Ragnarok (2011), her collection of short stories, Little Black Book of Stories (2003), and her latest short story 'Sea Story', she shapes posthuman subjects by delivering the enmeshed 'onto-stories' of humans, things, and gods.